Cancer Tissue Engineering: A Novel 3D Polystyrene Scaffold for In Vitro Isolation and Amplification of Lymphoma Cancer Cells from Heterogeneous Cell Mixtures. (5th September 2011) - Caicedo-Carvajal, Carlos E.; Liu, Qing; Remache, Yvonne; Goy, Andre; Suh, K. Stephen
Abstract : Isolation and amplification of primary lymphoma cells in vitro setting is technically and biologically challenging task. To optimize culture environment and mimic in vivo conditions, lymphoma cell lines were used as a test case and were grown in 3-dimension (3D) using a novel 3D tissue culture polystyrene scaffold with neonatal stromal cells to represent a lymphoma microenvironment. In this model, the cell proliferation was enhanced more than 200-fold or 20, 000% neoplastic surplus in 7 days when less than 1% lymphoma cells were cocultured with 100-fold excess of neonatal stroma cells, representing 3.2-fold higher proliferative rate than 2D coculture model. The lymphoma cells grew and aggregated to form clusters during 3D coculture and did not maintained the parental phenotype to grow in single-cell suspension. The cluster size was over 5-fold bigger in the 3D coculture by day 4 than 2D coculture system and contained less than 0.00001% of neonatal fibroblast trace. This preliminary data indicate that novel 3D scaffold geometry and coculturing environment can be customized to amplify primary cancer cells from blood or tissues related to hematological cancer and subsequently used for personalized drug screening procedures.